Georgia of 1991 -1999: The first signs of the Economic Sovereignty and an Economic Safety - David Aslanishvili (Modern Scientific Technology, 2025)
The declaration of independence of Georgia faced unprecedented economic problems for the population of Georgia, as this process was accompanied by internal unrest, civil strife and conflicts. As a result, the economy of Georgia faced actual destruction. In this regard, the reforms carried out in 1991-1999 are of particular importance in terms of the country's economic sovereignty and economic security.